Uma sequência didática do gênero poema: desafios e possibilidades para o aperfeiçoamento do letramento literário - Grassi, Marilu (2015)
This current study, of an applied nature, has investigated the applicability and the contributions of the teaching Sequence procedure as a resource to approach the reading of the discursive genre, poem, based on the promotion of the literary literacy. Through the methodology centered on action research, classroom interventions are described and analyzed, which are composed of 8th grade students of the of the public education system of a county of the countryside of Paraná / BR. The Bakhtin's conception of speech genres and the proposed teaching sequence Dolz, Noverraz and Schneuwly (2004) among others, form the basis of the theoretical reference. The observation of the participants has been used as instrument of collection, which has been supported by field report, videotaping, and students testimonials. We have found in the qualitative paradigm a viable way of development of this research, guided by the transformation of such situation. The data analysis points to the importance to the presence of the mediator on the training process of the reader, because, besides contributing to the interaction between the text and the reader, it intensifies the motivation to the reading, as well as to the textual production. It also shows that teaching sequence (TS) may be an effective methodology to support the educators on providing training to the literary literacy, once there has been positive changes on the behavior of the student as active interlocutor of the communicative process. Finally, the elaboration of this work, while action research allowed us to dialogue with important theories to our teacher training. So that, we expect that the results obtained here may collaborate to a thinking about the possibilities and improvements on the reading teaching of poems in the classroom